FINANCIAL INDICATORS AND MONEY SUPPLY IN NIGERIA - Kehinde Isiaq Olaiya; Abdul-Azeez Adeniyi Alao; Mayowa Ebenezer Ariyibi; Emmanuel Olufemi Adebayo (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: This study investigates the determinants of money supply (MS) in Nigeria, a volatile emerging economy, focusing on key financial indicators Net Domestic Assets (NDA), currency outside banks, demand deposits, and quasi-money and their implications for inflation control, liquidity management, and economic growth. Methods: The analysis applies advanced econometric techniques, including the Augmented Dickey-Fuller (ADF) test for stationarity and cointegration tests for long-run relationships. Although variables are non-stationary and not cointegrated, the Fully Modified Least Squares (FMOLS) method is employed to estimate long-term effects. Results: Findings show that demand deposits and quasi-money have significant positive effects on money supply, whereas NDA and other net assets exhibit negative relationships. This reflects the complex interplay between financial system components, liquidity conditions, and monetary dynamics. Conclusion and suggestion: The study emphasizes the roles of banking system confidence, liquidity levels, and domestic credit in shaping money supply. It recommends that policymakers adopt balanced monetary strategies to effectively manage liquidity, curb inflationary pressures, and support sustainable economic growth in Nigeria.